Calling the police from the 'ghetto': legal consciousness amongst ethnic minority parents. Issue 2 (3rd July 2021) - Madsen, Mads
ABSTRACT: Ethnic minority communities in Nordic countries are increasingly subject to stereotypical and proactive policing practices. These developments have inspired new research on police-community relations. This article presents findings on police cooperativeness amongst ethnic minority parents residing in a disadvantaged neighbourhood in Denmark, based on qualitative data from a ten-month field study. Taking a 'critical legal consciousness' approach, the analysis describes how the parents conceptualize the need to call the police based on their combined evaluation of 'problematic situations', expected outcome of involving the police and alternative actions they might take instead of calling the police. Although experiences of negative police encounters were found to be a key factor causing parents to be hesitant to call the police, certain situational factors were found to overrule such experiences and inspired cooperativeness. These are particularly those which parents described as dangerous or as threatening to the wider community. The article discusses whether ethnic minority parents' willingness to call the police reflects a larger process of internal social distancing between law-abiding residents and a minority of undesirable deviants. The findings have implications for improving police-community relations and provide nuanced insights into the social life of a marginalized community.